Binder jet 3D printing of 316L stainless steel: A Taguchi analysis of the dependence of density and mechanical properties on the printing parameters - M. Zago; G. Segata; M. Perina; A. Molinari (Journal of Materials Research and Technology)
Most of the research on Binder Jetting 3D Printing of AISI316L stainless steel has focused on optimizing the sintering cycle, with less emphasis on the effect of printing parameters on the properties in the sintered state. This study aims to investigate the influence of printing parameters on density, mechanical properties in both the green and sintered states. A Taguchi model was employed to experimentally study four parameters (printhead speed, dark body, powder applicator speed, and shell thickness) at three levels using an L9 orthogonal array. The results showed that green density ranged from 51.3% ± 0.9%–57.0% ± 0.9%, while a sintered density of 98.6% ± 0.08% was achieved. Mechanical testing revealed green strengths between 1.8 ± 0.1 MPa and 6.1 ± 0.8 MPa, while tensile tests provided yield strength of 175.1 ± 3.5 MPa, ultimate tensile strength (UTS) of 532 ± 9.7 MPa, and elongation at break of 87.7% ± 7.5%.ANOVA analysis indicated a statistically significant effect of the dark body (binder saturation) on density and mechanical properties. In the green state, increasing binder saturation enhances green density and bending strength. However, in the sintered state, higher binder saturation results in lower densification and UTS. Powder applicator speed also demonstrated statistical relevance for green density, where lower speeds produced higher density. Conversely, shell thickness and printhead speed had negligible effects on the properties investigated. These findings highlight the most significant printing parameters and their impact of target properties. Additionally, linear models were developed as a tool for optimizing printing parameters based on the desire density and mechanical outcomes.